Suffer the Little Children : Child Migration and the Geopolitics of Compassion in the United States - Casavantes Bradford, Anita (Book collections on Project MUSE., 2022)
"In this affecting and innovative global history-starting with the European children who fled the perils of World War II and ending with the Central American children who arrive every day at the U.S. southern border-Anita Casavantes Bradford traces the evolution of American policy toward unaccompanied children"--